THE EFFECTIVENESS OF ONLINE SERVICES AT THE DINAS KEPENDUDUKAN DAN CATATAN SIPIL, SIDOARJO DISTRICT (MAP Observer: Jurnal Penelitian Administrasi Publik, 2022)
PLAVON Dukcapil is one of the internet-based innovations from the Population and Civil Registration Office of Sidoarjo Regency in order to simplify and speed up the process of population administration services, namely population registration and civil registration that can be done independently. This study aims to find out how the effectiveness of online services (PLAVON) at the Population and Civil Registration Office of Sidoarjo Regency, and what factors support and obstacle in the Dukcapil PLAVON service. This type of research is a descriptive qualitative approach, namely by seeing, describing, and explaining the phenomenon directly. Based on this research, it can be seen that the online service (PLAVON) of the Sidoarjo Regency Population and Civil Registration Service runs effectively according to the effectiveness indicators in this study, namely indicators of program targeting accuracy, program socialization, program objectives and program monitoring. The supporting factor for implementing the program is the availability of infrastructure that supports the implementation of the Dukcapil PLAVON, while the factor that hinders the implementation of the program is the lack of human resources who handle PLAVON. The advice given is to carry out socialization intensively so that more people know and understand the existence of the Dukcapil PLAVON, and make maximum use of the existing human resources at the Population and Civil Registration Office.